eLingua : Issue 2 : August 2015 / Academy of Language Studies - Chone, Liaw Shun; Mohd Amin, Noraziah; Zulkifli, Che Nooryohana; Kudus, Nazima Versay; Ab. Rahim, Suzana; Razali, Wan Noorli; Ismail, Rushita; Yih, Mah Boon; Lee, Noor Azli Affendy; Nah, Er Ann; Chone, Liaw Shun; Aboo Bakar, Rofiza; et al. (Academy of Language Studies, 2015)
1. Hari Raya ‘Potluck’ Gathering 2015 2. Blended Learning & e-content (BLeC) UiTM Pulau Pinang 3. PhD Research Methodology (North Zone) 2015: PhD on Time 4. Our Victorious Team at KIK UiTMPP 2015 5. OBE Workshop 6. Editing Workshop for English Lecturers 7. APB MUET Seminar 2015 8. UiTM Kedah Colloquium 2015 9. eAttendance Workshop 10. A Day to Remembers UiTM PENANG ENGLISH LANGUAGE DAY 2015 11. Activity: Whose line is it anyway? (Movie Dubbing) 12. Activity: Lights, Camera, Action (Role-play) 13. ‘Program Khidmat Masyarakat APB UiTMPP 2015’ 14. URBAN French in Penang 15. Invention, Innovation & Design Exposition (iidex) 2015 16. Is There A Connection Altogether? 17. Menjadi Seorang Pakar Dalam Pengurusan Wang 18. From Bukit Mertajam to Padang Besar with Love